Model parameters of technical and tactical actions in the competitive activities of volleyball players - E.Iu. Doroshenko (Physical Education of Students)
The application of modeling of technical and tactical actions as one of the leading components of the control system of competitive activities of highly skilled volleyball players. It is show that the proposed modeling techniques can generate the optimum orientation of the training process with the use of specialized tools at different stages of the annual cycle of training. In a study based on official statistics volleyball tournament World League in 2012 years. It is recommended to be oriented on the followings model indexes of actions of command and sportsmen: general amount of the collected glasses (170 - 190); amount of glasses, collected in an attack (139 - 157); amount of glasses, collected at blocking (12 - 24); amount of glasses, collected from a serve (9 - 17); the middle index of efficiency is protective actions (at the reception of ball from a serve -58,29%). It is shown that the performance of technical and tactical actions can be used as a model in the management of the process of training and competitive volleyball elite athletes.